SISTEM DETEKSI KEBOCORAN PIPA DAN MONITORING DEBIT AIR MENGGUNAKAN FLOWMETER BERBASIS INTERNET OF THINGS - Moh. Wildan Ali Fikri; Raden Arief Setyawan; n/a Nurussa’adah (Jurnal Mahasiswa TEUB, 2023)
Water is a primary need for humans because of the fulfillment of survival. Water supply is a direct activity from PDAM to the community. Losses that often arise, namely leaks due to broken pipes or pipes that are not tight. leakage information is carried out by the public directly to the officer to check the pipe. Late repairs can result in wasted water. The development of technology in the 4.0 era has had a big impact on society. So, the researchers designed to create a pipe leak detection system and monitor water discharge using an internet of things-based flowsensor. This system uses 3 flowsensors. Flowsensor connected to NodeMCU. NodeMCU is connected to the thingspeak database via a Wi-Fi internet network. Readings by the flowsensor are received by NodeMCU then forwarded to Thingspeak to be displayed on the website page. This research was conducted with the hope of providing more accurate water discharge measurement results in detecting pipe leaks. Keyword: flowsensor, water flow, NodeMCU, leaks